Putting entrepreneurial process competence into the focus in entrepreneurship education: Experience from Estonian universities - T\~onis Mets; Mervi Raudsaar; Kaire Vahej\~oe; Merike Kaseorg; Piia Vettik-Leemet (Administrative Sciences, 2022)
Although entrepreneurship at the university level has constantly been evolving, little research has been done on what competencies should be developed in entrepreneurship education (EE) and how EE relates to the core of entrepreneurship - the entrepreneurial process competence. This article seeks to develop and empirically measure the entrepreneurial process competence in the context of EE. A self-assessment questionnaire based on the "generic" entrepreneurship competence model, improved with the section on entrepreneurial process competence, was used to assess the impact of EE intervention in major Estonian universities. The survey took place in two stages: the same questions were repeated at the beginning and end of the course in the 2019 autumn semester. It gave the responses of 355 students and showed the varied and small positive individual-level impact of entrepreneurship courses on minor aspects of "generic" competences in different universities, depending on training methodology, study volume and contact hours. At the same time, all the competencies of the entrepreneurial process grew significantly. Readiness to start own business did not change. The article recommends focusing on entrepreneurial process competencies and their acquisition for development and metrics of entrepreneurship learning progression.
Keywords: 350; competencies; entrepreneurial competence; entrepreneurial process; entrepreneurship education; generic competence; impact; self-assessment